Brain activity, low self-control, and delinquency: An fMRI study of at-risk adolescents. (May 2018) - Meldrum, Ryan Charles; Trucco, Elisa M.; Cope, Lora M.; Zucker, Robert A.; Heitzeg, Mary M.
Abstract: Purpose: A vast literature finds that low self-control is associated with a myriad of antisocial behaviors. Consequently, increasing attention has focused on the causes of low self-control. While criminologists have directed significant attention to studying its social causes, fewer studies have considered its neural bases. Methods: We add to this nascent body of research by using data collected on an at-risk sample of adolescents participating in the ongoing Michigan Longitudinal Study. We examine the functioning of prefrontal and limbic regions of the brain during failed inhibitory control, assessed using the go/no-go task and functional magnetic resonance imaging, in relation to low self-control and self-reported delinquency. Results: Results indicate that greater activation localized in the anterior cingulate cortex (ACC) during failed inhibitory control is negatively associated with low self-control. Moreover, the association between ACC activity and later delinquency is mediated through low self-control. Conclusions: Findings of this study demonstrate the utility of integrating neuroscientific and criminological perspectives on the causes of antisocial behavior. Concluding remarks address the theoretical and policy implications of the findings, as well as directions for future research. Highlights: Reduced anterior cingulate cortex (ACC) activity is associated with lower self-control. Lower self-control is associated with greater delinquency. Low self-control mediates the association between ACC activity and delinquency.